2019
DOI: 10.3892/etm.2019.7623
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end products and adipocytokines and oxidative stress in placental tissues of pregnant women with gestational diabetes mellitus

Abstract: Correlation between expression levels of advanced glycation end products (AGEs) and adipocytokines and oxidative stress index malondialdehyde (MDA) in placental tissues of pregnant women with gestational diabetes mellitus (GDM) was investigated. Seventy-two cases of GDM pregnant women who received routine prenatal examination and gave birth in the Department of Obstetrics, Binzhou City Center Hospital from March 2016 to May 2017 were collected as the observation group. Another 80 cases of normal pregnant women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…The adiponectin level in GDM patients was significantly lower than that in normal pregnant women ( 22 ). GA level in GDM patients was higher than that in normal pregnant women ( 23 ), consistent with the results of this study. It showed that the occurrence of GDM was related to adiponectin and GA, which had an effect on the pathogenesis of GDM.…”
Section: Discussionsupporting
confidence: 92%
“…The adiponectin level in GDM patients was significantly lower than that in normal pregnant women ( 22 ). GA level in GDM patients was higher than that in normal pregnant women ( 23 ), consistent with the results of this study. It showed that the occurrence of GDM was related to adiponectin and GA, which had an effect on the pathogenesis of GDM.…”
Section: Discussionsupporting
confidence: 92%
“…The systematic review and meta-analysis involved studies that reported the outcome measures at both first and second trimesters [ 32 ], first and third trimesters [ 36 ], second trimester [ 30 , 31 , 34 , 41 , 44 ], second and third trimesters [ 38 , 42 ], and third trimester of pregnancy [ 33 , 35 , 37 , 39 , 40 ] whereas two studies did not specify gestational period during sample collection [ 43 , 45 ]. Blood sample was collected from 13 studies [ 30 , 31 , 33 , 35 – 40 , 42 – 45 ], skin sample from two studies [ 32 , 34 ], and placenta sample from one study [ 41 ] ( Table 1 ). For analysis of specific AGEs and metabolic biomarkers, five and four studies were included to generate the pooled estimates of HOMA-IR [ 31 , 37 , 42 , 43 , 45 ], and HbA1c [ 31 , 33 , 37 , 43 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the geographical distribution, the review included seven studies from Europe [30][31][32][33][34][35][36], seven studies from Asia [37][38][39][40][41][42][43] and two studies from Latin America [44,45]. Thirteen of these studies employed case-control design [30,32,33,[35][36][37][38][39][40][41][42][43][44] whereas the rest three studies were cross-sectional in design [31,34,45]. Specifically, the meta-analysis of AGEs involved 774 cases and 834 controls.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The placenta of women with HIP is exposed to a high concentration of blood glucose at different degrees and windows of time. This may affect numerous cellular pathways, leading to accumulation of advanced glycation end-products (4,5) and induction of oxidative stress (6). The reported activation of the chronic hexosamine biosynthetic pathway (HBP) in placental tissue under similar conditions is also garnering attention (7).…”
Section: Introductionmentioning
confidence: 99%